Dampak Elektrifikasi Terhadap Pengeluaran Rumah Tangga di Kepulauan Seribu, Jakarta - Krisianto, Adi (Jurnal Ekonomi Kuantitatif Terapan, 2018)
This study analyzes the impact of electrification of small islands on community welfare by evaluating household expenditure in the Thousand Islands. In 2008, South Seribu Islands District enjoyed electricity for the first time through an undersea electricity cable from the mainland of Jakarta, while the North Seribu Islands District in 2012 for the second phase. This gradual electrification process indirectly creates treatment and control groups that are ideal for conducting impact evaluation research. We use the Difference in Difference method, where South Thousand Islands District is the Treatment Group and North Thousand Islands District as the Control Group, with the observation period from 2007 to 2012. We found that total household expenditure rose significantly in all observation periods as an impact of electrification . Second, we found differences in household responses to some types of their expenses. Food expenditure increased significantly throughout the observation period, while non-food expenditure increased only in the first and second year after electrification.
Keywords: Elektrifikasi, Difference in Difference, Pengeluaran Rumah Tangga, Kesejahteraan Rumah Tangga